Migration dynamics of polar bears (Ursus maritimus) in western Hudson Bay. (9th March 2021) - Bohart, Alyssa M; Lunn, Nicholas J; Derocher, Andrew E; McGeachy, David
Abstract: Migration is predicted to change both spatially and temporally as climate change alters seasonal resource availability. Species in extreme environments are especially susceptible to climate change; hence, it is important to determine environmental and biological variables that influence their migration. Polar bears ( Ursus maritimus ) are an Arctic apex carnivore whose migration phenology has been affected by climate change and is vulnerable to future changes. Here, we used satellite-linked telemetry collar data from adult female polar bears in western Hudson Bay from 2004 to 2016 and multivariate response regression models to demonstrate that 1) spatial and temporal migration metrics are correlated, 2) ice concentration and wind are important environmental variables that influence polar bear migration in seasonal ice areas, and 3) migration did not vary across the years of our study, highlighting the importance of continued monitoring. Specifically, we found that ice concentration, wind speed, and wind direction affected polar bear migration onto ice during freeze-up and ice concentration and wind direction affected migration onto land during breakup. Bears departed from land earlier with increased wind speed and the effect of wind direction on migration may be linked to prey searching and ice drift. Low ice concentration was associated with higher movement during freeze-up and breakup. Our findings suggest that migration movement may increase in response to climate change as ice concentration and access to prey declines, potentially increasing nutritional stress on bears. Abstract : Polar bears are migrating on challenging ice. Using spatial and temporal migration metrics, we show that bears move based on their environment. Bears depart land earlier with increased wind speeds. Wind direction may influence hunting and ice drift, affecting bear migration. We show that bears in low ice concentration areas travel more, potentially increasing energetic demands as climate change reduces sea ice and reduces access to prey.